1987
DOI: 10.1007/bf00120252
|View full text |Cite
|
Sign up to set email alerts
|

Notetaking and review: The research and its implications

Abstract: Notetaking and review are positively related to academic achievement, but many students record too few notes to benefit funy from these activities. This paper presents ten factors that may constrain notetaking and review, and provides corresponding implications for improving these study behaviors and for conducting further research. Some instructional implications are that students should record more extensive and conceptual notes and that instructors can help students by organizing their presentations, reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
1
13

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 57 publications
6
82
1
13
Order By: Relevance
“…Variations in cognition, within the working memory control processes influences note-taking, this is because information is held and manipulated there. Findings suggest students with low memory ability record smaller number of words, complete ideas [20]. To enhance achievement note-taking can be combined to study content, forming questions, this has been positively demonstrated [21].…”
Section: Cognition and Multimediamentioning
confidence: 96%
“…Variations in cognition, within the working memory control processes influences note-taking, this is because information is held and manipulated there. Findings suggest students with low memory ability record smaller number of words, complete ideas [20]. To enhance achievement note-taking can be combined to study content, forming questions, this has been positively demonstrated [21].…”
Section: Cognition and Multimediamentioning
confidence: 96%
“…DESCRIPTORS: college instruction, college students, guided notes, lecture notes, quiz performance _______________________________________________________________________________ Although research on note taking suggests that review of accurate, thorough, and organized notes is associated with better quiz performance (Kiewra, 1987), many college students do not produce adequate notes during lectures. In a randomly selected sample of 40 students in an introductory psychology course, Baker and Lombardi (1985) found that most students recorded about 50% of the main ideas targeted in a lecture and less than 25% of other relevant material.…”
mentioning
confidence: 99%
“…Using a paper notebook is important for several reasons. Writing helps the student remember and understand [7] and using paper rather than computers prevents distraction [13]. Moreover, users" notes combined with audio recordings proved to be a powerful means of indexing meetings [21] (a situation similar to lectures).…”
Section: Capturing the Classmentioning
confidence: 99%